The effect of adding nilem fish meat flour (Osteochilus vittatus) on the organoleptic preference level of Kembang Goyang - Junianto, Junianto; Humma, Fatbella Alyatul; Hartarto, Dwi; Fadillah, Tiara Siti (Acta Aquatica: Aquatic Sciences Journal, 2024)
Fish flour can be used for both substitution and partial fortification in raw materials such as wheat flour. The addition of nilem fish flour to kembang goyang can affect preference levels due to the resulting variations. This research aims to determine the appropriate level of adding nilem fish flour in making kembang goyang to obtain the most preferred product. This research is experimental research with data analysis using the Friedman test and Bayes test. The addition of nilem fish flour did not significantly affect the appearance and texture of kembang goyang in terms of organoleptic preference level. However, this affects the aroma and taste, where the higher the concentration of nilem fish flour added, the stronger the aroma and taste of kembang goyang.Keywords: Fortification; Kembang Goyang; Nilem Fish Meat Flour